Treatment retrograde ejaculation organic and functional origin - Knigavko, Oleksandr (My University, 2016)
The work is devoted the treatment of different for of retrograde ejaculation
Keywords: gialuronic acid gel; retrograde ejaculation; alfaadrenomimetics; Midodrine